Sаllunto–Bersumno–Scodra Roman Roads - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The paper presents data concerning Sаllunto–Bersumno–Scodra Roman roads (Riječani-Podgorica-Skadar) and intermediate communities in the southeastern parts of the province of Dalmatia. While researching ancient roads in the southeastern part of the province of Dalmatia (Montenegro), we relied on recorded oral sources, epigraph statues, milestones, bridge, and road remains in the area. We discussed also contemporary historiographers’ various opinions about the location of stations. Using the data obtained after visiting the area itself and the data from Peutingeriane and the Antonine Itinerary, we believe that the road led to the east from the Sаllunto station (Riječani) to Anderbu (Nikšić) and then to the Varis station (Povija), Halatu (Spuž), Bersumno (Podgorica), across the Cinna station (Vuksan-Lekić) into Scodru (Skadar). Archaeological remains (the Roman settlement and road remains and the fragments of milestones) found in Riječani, Nikšić, Podgorica, Tuzi, Vuksan-Lekić and Skadar (the southeastern parts of the province of Dalmatia) point out that this area was connected by the network of Roman roads. However, it is believed today that Publius Cornelius Dolabella started building the road network and that it was finished during the rule of Claudius, i.e., in 48 AD. All the other dates (the 3rd and 4th centuries) and inscriptions are related to the road repair or renovation. We, however, do not have enough records which would enable us to determine easily reliable and precise location of these stations today. Therefore, the systematic research of this area, left to be done, will enable us to do that.